2010
DOI: 10.1044/lle17.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Use of the LENA Tool to Evaluate the Effectiveness of a Parent Intervention Program

Abstract: This article describes a study investigating the language environment analysis (LENA) tool to measure the effectivenes of a parent intervention training program with children with language delays. In addition to the effects of parent training on the language development of participating children, the contributions of using LENA to measure growth also is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
6
1
1
Order By: Relevance
“…In contrast to the positive results of the previous studies, Weil and Middleton (2010) studied the effectiveness of an intervention program (It Takes Two to Talk: Hanen Program for Parents) using LENA and found no statistically significant improvements in either adult word counts, conversational turns, or child vocalizations from pre-intervention to post-intervention.…”
Section: Language Input Studies Usingcontrasting
confidence: 65%
“…In contrast to the positive results of the previous studies, Weil and Middleton (2010) studied the effectiveness of an intervention program (It Takes Two to Talk: Hanen Program for Parents) using LENA and found no statistically significant improvements in either adult word counts, conversational turns, or child vocalizations from pre-intervention to post-intervention.…”
Section: Language Input Studies Usingcontrasting
confidence: 65%
“…Both comparative and longitudinal studies measured the effects of treatment. Treatments including traditional speech therapy (Warren et al, 2010), formal established treatment programs such as Hanen's It Takes Two to Talk (Manolson, 1992;Weil & Middleton, 2011), and treatment associated specifically with provision of LENA feedback (Pae et al, 2016;Suskind et al, 2013). The remaining eleven cross-sectional studies often relied on a single day of recording.…”
Section: Type Of Studymentioning
confidence: 99%
“…The authors found that the intervention tested produced minimal effects on parent word count and conversational turns between parents and children. However, they found high levels of participant compliance with the method, suggesting that this naturalistic approach could be used to improve future parent interventions based on real behavioral data (Weil & Middleton, 2010).…”
Section: Overview Of Observational Ambulatory Assessment Methods For ...mentioning
confidence: 99%